A novel tracer technique to quantify the atmospheric flux of trace elements to remote ocean regions. Issue 2 (12th February 2015) - Kadko, David; Landing, William M.; Shelley, Rachel U.
Abstract: Atmospheric input into the global ocean constitutes an important budgetary component of numerous chemical species and plays a key role in controlling biogeochemical processes in the ocean. Assessment of this input is difficult, however, because measurements of deposition rates to the ocean, particularly in remote areas, are rare and susceptible to problems of temporal and spatial variability. While the collection and analysis of aerosol samples is somewhat routine, the chemical concentration data collected from ship board or land‐based aerosol samplers in and of themselves cannot yield the deposition flux of trace elements; a method is required to transform concentration measurements into flux. The ability to derive the atmospheric flux of 7 Be from its ocean inventory provides a key linkage between the atmospheric concentration of chemical species and their deposition to the ocean. We have demonstrated that estimates of the atmospheric flux of trace elements (TEs) can be made by multiplying the ocean inventory of 7 Be x [TE/ 7 Be] ratio in bulk aerosols. Flux estimates for trace elements made by the 7 Be ocean inventory method were comparable to fluxes derived from rain samples collected on the island of Bermuda. The situation at Bermuda allows such testing to be made, where ocean‐based methods can be calibrated by convenient land locations. Our results suggest that this method would be useful for remote areas where fixed sampling stations do not exist; that is, the majority of the global ocean. Key Points: Atmospheric input into ocean constitutes budgetary component of chemical species Assessment of the atmospheric input is difficult